ANALYSIS OF THE EFFECT OF U-TURN ON TRAFFIC FLOW PERFORMANCE - Sugianto, Martinus Agus; Rahman, Fazlur; Asy-syirozi, Mochamad Sahruddin; Nugraha, Rully Adi (International Journal of Social Service and Research, 2024)
This paper aims to explore the impact of U-turn motions on traffic flow and service levels. The research employs the Guidebook (PKJI, 2023) to assess observations related to traffic volume, vehicle speed, and both disturbed and undisturbed flow, which are gathered during the field survey. The data used for analysis was obtained by collecting primary data and secondary data according to the needs of the research. In addition, the data was obtained from a number of reports and documents that had been prepared, as well as the results of other literature studies. The results show that the number of vehicles on a road section is significantly increased, resulting in a significant increase in traffic volume and a decrease in vehicle speed. Moreover, the frequency of the use of the maneuvers affects the level of congestion on the road section, highlighting the need for early and strategic planning in the development of transportation infrastructure, particularly land transportation, which is crucial for facilitating everyday mobility and economic activities. This paper also highlights the importance of incorporating advanced traffic modeling techniques and simulations to enhance prediction of traffic behavior under different scenarios, informing infrastructure improvements and traffic management strategies. Finally, comparing findings with similar studies in other regions could yield valuable benchmarks for assessing traffic efficiency and service quality.